The gas bladder of Pantodon buchholzi: Structure and relationships with the vertebrae. (9th October 2020) - Icardo, José M.; Capillo, Gioele; Lauriano, Eugenia R.; Kuciel, Michal; Aragona, Marialuisa; Guerrera, Maria Cristina; Zaccone, Giacomo
Abstract: We report here on the histological and structural characteristics of the gas bladder, the vertebral morphology, and the bladder–vertebra relationships of the butterfly fish, Pantodon buchholzi . The bladder opens at the boundary between the pharynx and the esophagus by a middle slit. A pneumatic duct is absent. The bladder shows a dorsolateral wall that adapts to the anfractuosities of the coelomic cavity and a ventral wall in contact with the abdominal organs. The vertebral bodies are formed by an hourglass shaped autocentrum, and by an arcocentrum reduced to several longitudinal ridges. The transverse processes adopt the structure of a cage whose walls are formed by bone trabeculae of variable size and distribution pattern. The dorsolateral wall of the bladder is a membrane that covers the kidney, adapts to the irregular shape of the vertebrae, and invades the transverse processes at several points before extending laterally. However, invasion of the vertebral bodies, the presence of a labyrinth, or the formation of respiratory parenchyma were not observed. The luminal surface of this wall is a thin respiratory barrier containing a single epithelial cell type. In addition, the wall contains numerous eosinophils that may be implicated in immune defense. The bladder ventral wall is a membrane rich in collagen, vessels, smooth muscle, and nerves that lacks a respiratory barrier. Its luminal surface contains ciliated and nonciliated cells. The two cell types appear implicated in surfactant production. Abstract : Pantodon buchholzi . Scanning electron microscopy. Transverse body section at the level of the intervertebral ligament. Cranial view. In the midline, the bladder dorsolateral wall covers the cardinal posterior vein (black arrowhead), the kidney (K), the lateral sides of the vertebral body, and the transverse processes. The bladder enters the transverse processes through several large fenestra (arrows). Smaller fenestra in the transverse processes (asterisks) are covered. The membranous bladder extends laterally (white arrowheads) to cover the dorsal side of the coelomic cavity. The spinal cord (S) and epaxial muscles (M) are indicated.